Skrining dan Konseling Kesehatan Mental Emosional pada Mahasiswa Universitas Syiah Kuala - Hasmila Sari; Martina Martina; Sri Novitayani; Farah Dineva R (Pusat Riset dan Inovasi Nasional, 2025)
Emotional mental health is a state of overall psychological and emotional well-being, focusing on an individual's ability to understand, express, and manage feelings. Emotional mental health disorders can occur in anyone, including students, and may affect their daily activities and academic achievement. The purpose of this activity is to conduct emotional mental health screening among students using the SRQ-20 questionnaire, provide brief counseling to students with high scores (indicating emotional disorders), and increase knowledge and awareness among students about mental health and stress management. The method used was a Community-Based Service approach consisting of three stages: (1) activity planning, (2) implementation, and (3) evaluation and reporting. The results showed that 17 students (31.5%) showed indications of mild and moderate emotional mental disorders, while 9 students (16.6%) showed indications of severe emotional mental disorders. All participants with scores of ≥6 were followed up with brief counseling, and 10 of them were referred for further counseling at the university counseling center. This activity provided tangible benefits for students and strengthened the role of higher education institutions in supporting the psychological well-being of the academic community.